HDAC11, an emerging therapeutic target for metabolic disorders - Chen, Huizhen; Xie, Chunguang; Chen, Qiu; Zhuang, Shougang (Frontiers in Endocrinology, 2022)
Histone deacetylase 11 (HDAC11) is the only member of the class IV HDAC, and  the latest member identified. It is highly expressed in brain, heart, kidney and some other organs, and located in mitochondria, cytoplasm and nuclei, depending on the tissue and cell types. Although studies in HDAC11 total knockout mice suggest its dispensable features for tissue development and life, it participates in diverse pathophysiological processes, such as DNA replication, tumor growth, immune regulation, oxidant stress injury and neurological function of cocaine. Recent studies have shown that HDAC11 is also critically involved in the pathogenesis of some metabolic diseases, including obesity, diabetes and complications of diabetes. In this review, we summarize the recent progress on the role and mechanism of HDAC11 in the regulation of metabolic disorders, with the focus on its regulation on adipogenesis, lipid metabolism, metabolic inflammation, glucose tolerance, immune responses and energy consumption. We also discuss the property and selectivity of HDAC11 inhibitors and their applications in a variety of in vitro and in vivo models of metabolic disorders. Given that pharmacological and genetic inhibition of HDAC11 exerts a beneficial effect on various metabolic disorders, HDAC11 may be a potential therapeutic target to treat chronic metabolic diseases.